The Rise of Interfaith Dialogue: Social Media, Youth, and Religious Inclusivity in Indonesia - Juhri, Muhammad Alan (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2024)
This paper investigates how interfaith dialogue discourse is now developing significantly with the role of social media and youth. Based on online research and virtual ethnography, this paper argues that creatively utilizing social media with involving youth as media-savvy is the main factor in significantly increasing the acceptance of interfaith dialogue discourse. In-depth content analysis with a focus on interfaith dialogue through YouTube podcasts reveals several strategies applied by the creator. This paper highlights several strategies, namely using hashtag and maximizing thumbnail, propagating podcasts with clickbait titles, consistenly uploading content, and connecting with other platforms. In addition, youth involvement also plays an important role in achieving significant interfaith dialogue such as by engaging them with humor and comedy, eye-catching appearance and millennial style, and visual persuasion. Finally, great acceptability achieved by interfaith podcasts on youtube has proven the existence of religious inclusivity in Indonesia.